The impact of clothing style on bone mineral density among women in Turkey - (:unkn) unknown (SPRINGER, 2008)
To investigate the effect of veiled clothing style on bone mineral density (BMD). The BMD measurements were performed on the femoral neck and the lumbar spines of adult female population with two different types of clothing taking calcium daily in the normal range according to the proper technique utilizing dual energy X-ray absorptiometry (DEXA). In the lumbar spine measurements, the BMD was measured 1.0020 +/- 0.177 gr/cm(2) in cases with veiled clothing style while it was measured 1.0793 +/- 0.169 gr/cm(2) in cases with unveiled clothing style (P = 0.049, t = 1.98). In the femoral neck measurements, the BMD was measured 0.8428 +/- 0.146 gr/cm(2) in cases with veiled clothing style while it was measured 0.8532 +/- 0.177 in cases with unveiled clothing style (P = 0.548, t = 0.457). Although a decrease in BMD values was observed in both regions with veiled clothing style, only the change in the lumbar spine BMD measurements was statistically significant. These findings suggest that the veiled clothing style may have an adverse effect on BMD by interfering with the sun exposure which is believed to have a key role in bone strength.
Keywords: DEXA; BMD; Turkish women; veiled clothing style; X-RAY ABSORPTIOMETRY; PROXIMAL FEMUR; POSTMENOPAUSAL OSTEOPOROSIS; AXIAL SKELETON; LUMBAR SPINE; CALCIUM SUPPLEMENTATION; RELATIVE CONTRIBUTIONS; RENAL OSTEODYSTROPHY; PREMENOPAUSAL WOMEN; VERTEBRAL DENSITY